STRATEGI BERTAHAN HIDUP MASYARAKAT PESISIR BALI SELATAN DI ERA MODERNISASI - Riwanto, Riwanto (Widyadari: Jurnal Pendidikan, 2019)
The strategy of developing the tourism industry on the one hand has been able to improve the standard of living of Balinese people towards better development, but on the other hand raises new problems, especially for community members who are unable to compete directly in the increasingly widespread development of the Bali tourism industry. social that there are some local people who really don't have much involvement in the development process of the tourism industry that continues to grow.           Determination of informants in this study using snaw balling sampling techniques, data collected using non-participation observation methods, in-depth interviews, and recording documents, then the collected data is dissected with an exchange theory developed by George Caspar Homans.           The results revealed that there were some Balinese who were unable to compete directly involved in the growing development of the tourism industry in Bali so that some Brawa Beach women in Tibubeneng Village, Kuta Utara District chose a profession as fishermen, and some of the Grahasanti Hamlet in Sidakarya Village, South Denpasar Subdistrict chose a profession as salt farmers. The choice of profession is due to the low level of education, the natural environment that supports the profession, and economically the profession is enough to benefit them.